Legibility of neighborhood parks and its impact on social interaction in planned residential areas in Putrajaya, Malaysia - Moulay, Amine (2015)
Public park is one of the principle elements in a cityscape. A neighborhood park within a planned residential area has a significant role in strengthening social interaction by providing residents with various opportunities for leisure and community activities. However, in many situations, these parks are not fully utilized to the benefits of the users. Studies have indicated that social interactions in public spaces within planned residential areas are not at a satisfactory level. The parks are not fully responsive to the needs of the users because of its inability to attract them to visit. This could be due to the lack of legible elements that make the parks physically and visually unattractive for social activities. The aim of this research is to examine legibility of neighborhood parks and its impact on social interaction. Legibility, defined as the apparent clarity of the cityscape, is an essential attribute in making public spaces responsive to the social needs. This study was conducted in the Precinct 8 and Precinct 9 neighborhoods parks, in a planned residential area in Putrajaya, Malaysia. Quantitative methodology was applied to measure the impact of the legibility attributes (clear structure, view obstacles, accessibility and visual aesthetic) on social interaction (park engagement and type of contact) within the parks. Questionnaire surveys were conducted with 378 respondents who were randomly selected among the neighborhood parks’ residents of the Precinct 8 and the Precinct 9. In addition, a cognitive mapping was conducted to support the survey results. To clarify the survey results, qualitative data from field observations were recorded in a form of notes and photographs to understand the real condition of the study areas. This research suggests that legibility of the neighborhood parks influences the duration of park use among residents which in turn could encourage social interaction. The clarity of the structure of the parks was mainly defined by the quality of the paths and the landmarks, while the accessibility was influenced by the number of entrances. The research identified that the visual obstacles were influenced by the quality of the edges, the distance between park’s activities and the overall form and shape of the park. The finding proves that the intensity of social interaction within the neighborhood parks is as a result of the combination between the legibility attributes and certain critical population density of the residential areas. These research findings contribute to the development of physical aspects of park design to increase social activities among the communities that could strengthen the social ties among residents. The study denotes the importance of legibility in the planning and design of public spaces that are responsive to the social needs of the urban communities.